An Overview on Biometric Authentication (International Journal of Food and Nutritional Sciences, 2022)
The words "bio" (life) and "matron" are the origin of the phrase "biometrics" (measurement). As a consequence, it involves measuring a user's distinctive traits in order to identify or authenticate them. By using the user's distinctive traits, such as a fingerprint scan, facial imaging, signature, or voice recognition, biometric identification verifies a user's identity to sign in to an account or get access to personal information. We currently witness a lot of cases of cybercrime, data breaches, data manipulation by unauthenticated individuals, hacking of personal accounts, and so forth since traditional password-based security techniques are hackable. In order to address these security concerns, a more secure system is necessary. Biometric authentication technology offers a different approach that cannot be circumvented because it uses software to identify or validate the user by comparing the data being fed with digital images of the user's distinctive characteristics. This information can't be copied or hacked, therefore it increases identification accuracy.